HISTORICAL AND CULTURAL CONTEXTS OF FEMININE TERMS IN LITERATURE - Milikova Maftuna Akmaljanovna; Rustamova Adash Eshankulovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article conducts a comprehensive comparative analysis of feminine terms within the realms of Uzbek and English literature, aiming to unravel the intricate layers of gender representation in these diverse linguistic and cultural contexts. Through a meticulous examination of lexical choices, semantic nuances, and cultural connotations embedded in feminine expressions, the study explores the ways in which societal norms and historical influences shape the portrayal of women. Employing a cross-cultural lens, the research investigates both commonalities and disparities in the linguistic construction of femininity, shedding light on the impact of cultural paradigms and linguistic structures on gender discourse. By drawing on a wide range of literary works from both traditions, the analysis captures the evolving dynamics of feminine representation, considering the influence of globalization and the exchange of cultural ideas on these linguistic landscapes.